2019
DOI: 10.24109/2176-6681.rbep.98i249.2830
|View full text |Cite
|
Sign up to set email alerts
|

Institucionalização da formação docente: análise de um programa de desenvolvimento profissional

Abstract: Este estudo tem como objetivo principal analisar, com base na literatura discutida, a institucionalização de um programa de desenvolvimento profissional de uma universidade federal brasileira, com vistas a identificar seu nível de consolidação, bem como a concepção dos docentes sobre ele. Adotou-se como metodologia a pesquisa qualitativa e foram utilizadas, para coleta de dados, a análise documental e a aplicação de questionário estruturado aos docentes participantes do programa. O referencial teórico que emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…Efforts toward making PTAs institutionalized are important; their institutionalization promotes a sense of teaching support and appreciation (48,59). Some progress is taking place at HEIs in Brazil in the form of isolated cases, since there is no national guidance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts toward making PTAs institutionalized are important; their institutionalization promotes a sense of teaching support and appreciation (48,59). Some progress is taking place at HEIs in Brazil in the form of isolated cases, since there is no national guidance.…”
Section: Resultsmentioning
confidence: 99%
“…Some progress is taking place at HEIs in Brazil in the form of isolated cases, since there is no national guidance. However, a recent study of one Brazilian university showed that, although there was an institutionalized pedagogical training program, it focused mostly on administrative and technical issues rather than on changes to the very core of teachers activities (59). Nevertheless, the program mentioned is relatively new, approximately 10 yr old, and it has made improvements over the years since its creation (59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Como se depreende, percebemos as Assessorias Pedagógicas Universitárias como dispositivos de apoio, cujas práticas de intervenção, de animação e de orientação se entrelaçam às práticas pedagógicas docentes, não as deixando isoladas (Lucarelli, 2007). A Assessoria Pedagógica Universitária representa, portanto, o lugar da Pedagogia Universitária e, por isso, precisa de ser um espaço legitimado (Broilo, 2015;Xavier, Toti & Azevedo, 2017) e comprometido institucionalmente (Cunha, 2014).…”
Section: Cartographie De La Formation Pédagogique Des Professeurs D'uunclassified
“…Além da carência por formação, os professores em exercício, em diferentes áreas, são egressos de processos formativos que oportunizaram a aquisição de conhecimentos majoritariamente teórico-procedimentais. Esta realidade gera uma demanda pelo desenvolvimento de competências didático-pedagógicas para a qualificação da formação profissional relativas aos conhecimentos, habilidades e atitudes necessárias ao exercício da docência (ALARCÃO, 2003;ALARCÃO;ROLDÃO, 2014;CORTELA, 2016;CUNHA, 2008CUNHA, , 2010aMELLO;FREITAS, 2018;MELO;CAMPOS, 2019;PIMENTA;ANASTASIOU, 2014;PIMENTA, 2012;SCREMIN;ISAIA, 2018;TORRES;ALMEIDA, 2013;XAVIER;TOTI;AZEVEDO, 2017).…”
Section: Introductionunclassified